IMPROVEMENT OF KINEMATIC CALCULATIONS OF METAL-CUTTING MACHINES TRANSMISSIONS - D.A. RUDIKOV (Advanced Engineering Research, 2010)
The design and specifying kinematic calculations techniques allowing to define the ratio and teeth numbers of the constant pair that meet the accuracy requirements of some metal-cutting machines by cost and time minimization are offered.